2006
DOI: 10.1007/s00284-005-0417-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Calcium and Magnesium on the Activity of Bovicin HC5 and Nisin

Abstract: Some Gram-positive bacteria produce small peptides (bacteriocins) that have antimicrobial activity, but many bacteria can become bacteriocin resistant. Bovicin HC5, a lantibiotic produced by Streptococcus bovis HC5, has the ability to inhibit nisin-resistant bacteria. Because nisin resistance has in many cases been correlated with an alteration of lipoteichoic acids or the polar head groups of membrane phospholipids, we decided to examine the effect of divalent cations on nisin and bovicin HC5 activity. Both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Addition of large amounts (100 mM) of Ca 2+ and Mg 2+ has been reported to counteract bacteriocin-mediated K + loss from Streptococcus bovis JB1. Calcium was found to be more effective than magnesium in reducing nisin activity, but the reverse was true with bovicin HC5 [14]. The latter is in agreement with our observation with enterocin LR/6, where Mg 2+ was comparatively more effective.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Addition of large amounts (100 mM) of Ca 2+ and Mg 2+ has been reported to counteract bacteriocin-mediated K + loss from Streptococcus bovis JB1. Calcium was found to be more effective than magnesium in reducing nisin activity, but the reverse was true with bovicin HC5 [14]. The latter is in agreement with our observation with enterocin LR/6, where Mg 2+ was comparatively more effective.…”
Section: Discussionsupporting
confidence: 91%
“…One such factor identified is the presence of cations. Divalent (Mg 2+ and Ca 2+ ) and trivalent (Gd 3+ ) cations are reported to inhibit the action of bacteriocins [8,14]. A similar protective effect was recorded on the action of enterocin LR/6 against M. luteus and Enterococcus sp.…”
Section: Discussionmentioning
confidence: 75%
“…These divalent cations have also been reported to decrease bacteriocin activity (Davies et al, 1996;Houlihan and Russel, 2006;Kumar and Srivastava, 2011). For L. monocytogenes, Davies et al (1996) reported that nisin resistance was associated with binding of divalent metals by ribitol and glycerol phosphates of lipoteichoic acids on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Cole, Darouiche, Legarda, Connell and Diamond (2000) showed that divalent ions such as magnesium (Mg 2+ ) and calcium (Ca 2+ ) could inactivate (from 10 mM) pleurocidin from a marine fish. Human defensin, some bacteriocins and cecropin–mellitin hybrids are strongly affected by magnesium, and can be inactivated even at a low Mg 2+ concentration (5 mM) (Friedrich, Scott, Karunaratne, Yan & Hancock 1999; Houlihan & Russell 2006). Seawater has a particularly high Mg 2+ concentration (ca.…”
Section: Discussionmentioning
confidence: 99%